2016
DOI: 10.1364/oe.24.001723
|View full text |Cite
|
Sign up to set email alerts
|

Calibration-free wavelength-modulation spectroscopy based on a swiftly determined wavelength-modulation frequency response function of a DFB laser

Abstract: A methodology for calibration-free wavelength modulation spectroscopy (CF-WMS) that is based upon an extensive empirical description of the wavelength-modulation frequency response (WMFR) of DFB laser is presented. An assessment of the WMFR of a DFB laser by the use of an etalon confirms that it consists of two parts: a 1st harmonic component with an amplitude that is linear with the sweep and a nonlinear 2nd harmonic component with a constant amplitude. Simulations show that, among the various factors that af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…However, unlike previous investigators [3,4,6], we report here an alternative use of trigonometric series postulated by Gabor [8] for representation of an arbitrary elementary signal.…”
Section: Theoretical Modelmentioning
confidence: 87%
See 2 more Smart Citations
“…However, unlike previous investigators [3,4,6], we report here an alternative use of trigonometric series postulated by Gabor [8] for representation of an arbitrary elementary signal.…”
Section: Theoretical Modelmentioning
confidence: 87%
“…Here α k , β k , φ k and ψ k are amplitudes and phase shifts, respectively, of the corresponding term (Gabor function) and G w is a width-adjusted (reduced) Gaussian distribution function described below in more details, see (6).…”
Section: Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Later Z. Qu has applied this idea successfully to CF-WMS [16,22,23]. Recently, in order to further consider the nonlinear response to the modulation, G. Zhao empirically suggested that the CMWR consists of two parts: a 1 st harmonic component with a linearly time-dependent amplitude and a nonlinear 2 nd harmonic component with a constant amplitude that can be expressed as [24] θ is the phase difference between the first and second harmonic of frequency modulation. This is here referred to "the Zhao's method".…”
Section: Introductionmentioning
confidence: 99%
“…This is here referred to "the Zhao's method". In [24], G. Zhao et al presented a comparison between these three models when fitted to an experimental spectrum. The results showed that the Zhao's method, due to its more completed description, obtained a smaller residual than others.…”
Section: Introductionmentioning
confidence: 99%